2003
DOI: 10.1097/01.ju.0000070437.14275.e0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Routine Repeat Transurethral Resection for Superficial Bladder Cancer: A Long-term Observational Study

Abstract: These data suggest a favorable outcome regarding recurrence and progression in patients with superficial bladder cancer who undergo ReTURB. ReTURB is suggested at least in those at high risk when bladder preservation is intended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
144
4
13

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 268 publications
(176 citation statements)
references
References 17 publications
10
144
4
13
Order By: Relevance
“…Patients who had a history of a previous TUR, high-grade tumor and intravesical therapy were excluded from the study in order to establish a homogeneous group of patients and to avoid the effect of intravesical treatment on recurrence. In univariate and multivariate analyses, in accordance with the literature, the presence of tumor multiplicity and MP presence were determined as the factors predicting recurrence (6,11,12,15,20,21). Recurrence has been shown to be statistically significantly more frequent in patients with non-MP ( Table 2).…”
Section: Mariappan Et Al (6) Have Demonstrated That (I) Multiplicitysupporting
confidence: 54%
See 1 more Smart Citation
“…Patients who had a history of a previous TUR, high-grade tumor and intravesical therapy were excluded from the study in order to establish a homogeneous group of patients and to avoid the effect of intravesical treatment on recurrence. In univariate and multivariate analyses, in accordance with the literature, the presence of tumor multiplicity and MP presence were determined as the factors predicting recurrence (6,11,12,15,20,21). Recurrence has been shown to be statistically significantly more frequent in patients with non-MP ( Table 2).…”
Section: Mariappan Et Al (6) Have Demonstrated That (I) Multiplicitysupporting
confidence: 54%
“…High residual tumor rate and tumor upstaging rates of 40-51% were observed in non-MP stage pT1 patients (14,15,16,17). The absence of MP has been shown to be associated with increased risk of early recurrence, even in low-grade pTa tumors (6).…”
Section: Mariappan Et Al (6) Have Demonstrated That (I) Multiplicitymentioning
confidence: 99%
“…The authors mentioned the reduced activity of immune system by age as the cause of poorer survival rates and higher risk of progression (6). In that study, the authors did not mention any information on performing a second TUR in their population, a factor which is associated with decreased recurrence and progression rates as well as better response to BCG (13,14). In our study, all patients similarly received maintenance BCG, besides, all patients underwent a second TUR.…”
Section: Discussionmentioning
confidence: 85%
“…28 After 5 years of follow-up in 124 patients, Grimm and colleagues found that 63% of those who underwent a repeat TURBT had tumour-free bladders compared with 40% of those who did not. 29 Similarly, a recent study demonstrated that a restaging TUR improved initial response to intravesical immunotherapy. 24 We recommend that a second TUR should always be performed 4 to 6 weeks after the initial resection when the initial TUR is incomplete or a T1 tumour is detected in the absence of muscularis propria in the specimen (Grade A recommendation).…”
Section: Second Turbtmentioning
confidence: 99%